A Comparative Study of Labor Relations Laws between China and Vietnam from a Regional and National Perspective: A Case Study of Tianhong Galaxy Textile Company (Journal of humanities and social sciences exploratio, 2025)
This paper adopts the perspective of regional and national studies, focusing on the adaptive challenges of China’s labor governance model within the Vietnamese legal context. By constructing a two-dimensional analytical framework of "institutional logic–cultural filtering," it reveals the deep-seated conflicts in governance logic between China and Vietnam in the field of labor relations law. The study finds that China’s "efficiency-first" model exhibits three types of fissures within Vietnam’s "social protection" framework: functional dislocation of texts, procedural formalism, and incommensurability of values. This paper advocates rigid compliance with core institutions, flexible retention of management processes, and creative transformation of cultural interfaces, providing empirical reference for cross-border labor governance under the Belt and Road Initiative.
Keywords: Regional and national studies; Labor law; China-vietnam comparison; Chinese textile enterprises